Perusahaan Keluarga, Koneksi Politik & Kinerja Perusahaan - Lidya Utamaningsi (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
Family businesses dominate the private sector in Indonesia and contribute 13.4% of the country's GDP. The family company has a longer investment horizon than the shareholders because the founder wants to continue bequeath the company to subsequent generations. To achieve these objectives the company will try to overcome the company's external constraints. The trick is through political connections. With a political connection the company will get various benefits so that it will ultimately contribute to the company's performance. This paper is a literature review of family businesses and political connections. Based on the results of the study, the researchers concluded that the family company had better performance than the non-family company. Politically connected companies have better performance than companies that are not politically connected during the reign of politicians concerned. Politically connected family companies have better performance than politically connected family companies.